Coupling distinct MOLP interactive approaches with a novel DEA hybrid model - Henriques, Carla; Luque, Mariano; Marcenaro‐Gutierrez, Oscar (International transactions in operational research, 2022)
We propose a modelling framework which allows considering different priorities and individual expansion and contraction scales for distinct types of inputs and outputs, through the Weighted Russell Directional Distance Model (WRDDM). An equivalence model between the WRDDM and the super‐ideal point model has also been established, which is then incorporated into several interactive Multiobjective Linear Programming (MOLP) approaches. The use of these diverse interactive methodologies allows obtaining the benchmark Decision Making Units (DMUs) which best suit the decision maker's (DM) preferences. This feature can be useful since traditional Data Envelopment Analysis (DEA) models tend to completely neglect the DM's preferences and value judgements in the computation of the DMUs used as a reference of best practices. Therefore, with this tool the DMs have the possibility of translating into the decision‐making process management constraints (namely, budgetary) and aspiration levels regarding the inputs and outputs, providing much more realistic support for actual decision‐making.